Development of Packaging Forming Machine from antimony leaf for Environment (Case Study: Mae Hong Son Province) - Kitipattanawit, Jetsadapol; Chainun, Chaicerd; Saksangn, Napamin; Rinsangpin, Manaspsn (Community and Social Development Journal, 2021)
The research on the development of packaging machine for the environment from antimony leaves (case study: Mae Hong Son province) is a research and development. The objectives are 1) To maximize the efficiency of antimony leaf materials for maximum benefit, solving the smog problem in Mae Hong Son province. 2) Design and develop packaging machines from antimony leaves 3) To test the effectiveness of packaging from antimony leaves to wrap food and study the satisfaction of the packaging obtained from the forming of 0the people in the community, Mae Hong Son province. Population and sample group used in the research are 1) Antimony leaves from the area. Mae Hong Son province. 2) Experts in examining the form of product for the packaging forming machine for the environment from antimony leaves, consisting of 3 people. 3) The target group for product testing is the group of people interested in the packaging machine for the environment. From antimony leaves and natural packaging, amount 100 persons. The research instruments were a semi-structured interview form. Assessment form for the effectiveness of packaging from antimony leaves to wrap food Data were analyzed by percentage, average, and standard deviation. The qualitative data used content analysis. The results showed that the test of the effectiveness of packaging from antimony leaves in food wrapping (3 fresh leaves overlapping) using prepared wet glue powder as a binder, should take time and heat. 140 degrees / 3 minutes to be able to ง form and set the packaging of antimony leaves in fresh leaves and It was found that the effectiveness of the packaging from antimony leaves in food wrapping (3 dry leaves overlapping) using the prepared wet glue as a binder, should take time and heat. 140 degrees / 2 minutes. If it takes longer than this, it will cause the leaves to dry out. So can form and set the packaging of antimony leaves in fresh leaves and studying the satisfaction of packaging from the forming of people in the community, Mae Hong Son province, found that the satisfaction of the packaging obtained from forming of people in the community, Mae Hong Son Province. The packaging is unique, beautiful, outstanding, average overall 4.53